Erfolgreiche Nachverhandlung des Freihandelsvertrags mit Mexiko - Christoph Scherrer (Wirtschaftsdienst, 2020)
Das Freihandelsabkommen zwischen den USA, Mexiko und Kanada in der Nachfolge zum NAFTA ist seit Beginn 2020 Gesetz in den USA. Das Abkommen wird sowohl von den betroffenen Wirtschaftsbereichen als auch von den Gewerkschaften unterstützt. In den vom Kongress erzwungenen Nachverhandlungen wurden insbesondere arbeitsrechtliche Vorschriften vereinbart, die vor Lohndumping aus Mexiko schützen sollen. Diese Vorschriften könnten für weitere Handelsabkommen Vorbild sein. – – In early 2020, the United States-Mexico-Canada Agreement (USMCA) became law in the USA. The Democrats' support for this free trade agreement, renegotiated by the Trump administration, is mainly due to the fact that they have tied in unprecedented monitoring and enforcement mechanisms to reform Mexican labour law. These mechanisms have been welcomed by the AFL-CIO and most - though not all - US trade unions. The hope is that strengthening the rights of Mexican workers will discourage corporations from moving jobs to Mexico. The article describes these innovative elements and presents an assessment by labour and trade specialists.
Keywords: F13; F16; F55; 330